Students’ Attitudes and Learning Preferences: A Need Analysis for CLIL Materials in EFL Primary Schools - Khoiriyah; Widodo, Estu; Mafruudloh, Naajihah (VELES Voices of English Language Education Society, 2025)
A thorough need analysis (NA) is essential for designing effective instructional materials, particularly in the context of Content and Language Integrated Learning (CLIL) for English as a Foreign Language (EFL) primary school students. Despite the increasing demand for ready-to-use CLIL materials, little research has explored the specific needs of students in this context. This study employed a Research and Development (R&D) approach, focusing on the NA phase to gather insights into students’ attitudes and material preferences for CLIL instruction. A total of 93 EFL primary school students participated in the study, with data collected via an online questionnaire that addressed two key aspects: students' attitudes toward learning English and their needs for learning materials through the CLIL approach. The data were analyzed using basic statistical methods in JASP software. The results indicated that while students generally hold a positive attitude toward learning English—particularly regarding its importance, their intention to continue learning, and intrinsic motivation—they do not consider English their preferred subject, and their interest in CLIL-related activities remains moderate. Regarding material needs, students preferred interactive and engaging methods, particularly through multimedia resources, group work, and technology integration. They also prioritized improving listening and vocabulary skills. Additionally, students showed strong interest in topics related to personal experiences and global issues, such as leisure activities, nature, and sports, while displaying less enthusiasm for academic subjects like geography and literature. These findings offer helpful input for developing digital CLIL materials better aligned with young learners’ interests and learning preferences.